Sustainable Agriculture for Alaska and the Circumpolar North: Part III. Meeting the Challenges of High-Latitude Farming - Stevenson, Kalb T.; Rader, Heidi B.; Alessa, Lilian; Kliskey, Andrew D.; Pantoja, Alberto; Clark, Mark; Smeenk, Jeffery (ARCTIC, 2014)
Agriculture is a severely underdeveloped industry in Alaska and throughout most of the Subarctic. Growers and entrepreneurs must overcome a diverse set of challenges to achieve greater sustainability in northern communities where resilience is threatened by food insecurity and challenges to northern agriculture have limited the industry. However, several field-based or social policy solutions to problems of high-latitude agriculture have been proposed or are being put into practice. Field-based solutions include the use of special infrastructure or farm management strategies to extend the short growing season, improve soil quality, integrate appropriate pest and irrigation management practices, and further develop the livestock sector. Social and policy solutions are resolutions or decisions reached by stakeholders and government, often through cooperative interaction and discussion. These solutions stem from meaningful discussion and decision making among community members, organizations, agencies, and legislators. Social and policy solutions for Alaska include addressing the high costs of land and the preservation of agricultural lands; improved markets and market strategies; more appropriate funding for research, education and infrastructure; and other integrative or cooperative efforts. Collectively, these solutions will work to improve the outlook for sustainable agriculture in Alaska. En Alaska et dans une grande partie des régions subarctiques, l’agriculture est une industrie extrêmement sous-développée. Les producteurs et les entrepreneurs doivent surmonter un ensemble de défis variés pour donner lieu à une plus grande durabilité dans les collectivités nordiques, là où la résilience est menacée par l’insécurité alimentaire et où les défis caractérisant l’agriculture nordique imposent des restrictions à l’industrie. Cependant, plusieurs solutions apportées sur le terrain ou par le biais de politiques sociales vis-à-vis des problèmes touchant l’agriculture en haute latitude ont été proposées ou sont en ...